Strengthening the Competitiveness of BUMDes Sumber Kamulyan through Digital-Based Management and Marketing Strategies - Anis Susanti; Risanda A. Budiantoro; Febrianur I.F.S. Putra; Binta Zulfa Nafisa; Abdullah Arif Nurhikmah; Enggarningtyas Retno Pinasti; Nadia Faiza Az Zahra (Unram Journal of Community Service, 2025)
Village-Owned Enterprises (BUMDes) have the potential to strengthen local economic competitiveness but often face challenges in governance and digital marketing. This community service program aimed to enhance the capacity of BUMDes Sumber Kamulyan in Wunut Village through the implementation of SIBUMDes Wunut, a website-based information system designed as an appropriate digital tool. The activities were carried out in five stages: initial governance and marketing management, intensive training for 30 participants consisting of village officials, BUMDes managers, women’s groups, and youth organizations, technology implementation, mentoring and evaluation, and sustainability planning. Evaluation using the Total Criteria of Response method indicated an average score of 86.75 percent, categorized as very good. The results showed improvements in management, including digital standard operating procedures and transparent financial recording, and in marketing, particularly through social media content development and tourism branding of Umbul Pelem. Sustainability is supported by the formation of an internal digital management team and partnerships with local stakeholders. In conclusion, SIBUMDes Wunut as a website-based system effectively improves governance, strengthens digital marketing strategies, and enhances the competitiveness of rural enterprises.